2011
DOI: 10.1057/dbm.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of customer loyalty in Pakistan's telecommunication industry

Abstract: is enrolled as a PhD Scholar at the Faculty of Management Sciences, International Islamic University, Islamabad. She is an ORACLE certifi ed professional and is currently pursuing an interest in research in the fi eld of psychological contracts, job scope, culture and absenteeism. Ms Fatima is currently engaged as faculty member at the International Islamic University, Islamabad. M. Bashir Khan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…In other words, the difference between the mean scores and the percentage scores is that the former takes into account the weight of the responses while the latter does not. Therefore, mean scores are a better indicator for ranking the factors (Sadia, Tasneem, & Khan, 2011;Metawa & Almossawi, 1998).…”
Section: Research Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the difference between the mean scores and the percentage scores is that the former takes into account the weight of the responses while the latter does not. Therefore, mean scores are a better indicator for ranking the factors (Sadia, Tasneem, & Khan, 2011;Metawa & Almossawi, 1998).…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…With regard to satisfaction, the outcome of the study suggests that satisfaction plays an important role in determining customer commitment for service providers and there is a positive correlation between improving customer satisfaction and gaining customer loyalty. Sadia, Tasneem, & Khan (2011) examined customer loyalty in the telecommunication industry in Pakistan, using 146 cell phone users. The study found that customer loyalty is shaped mainly by: trust, service quality, staff loyalty, and switching cost.…”
Section: Customer Satisfaction In Mobile Telecom Industrymentioning
confidence: 99%
“…Hence, businesses must increase the level of customer satisfaction by upgrading service quality, which in turn influences purchase and repurchase intentions in ISP markets (Seth et al, 2008). Customer commitment was found to explain customer loyalty behaviours in Pakistan's telecommunication service (Jahanzeb et al, 2011). Emotional commitment was found to be positively related to attitudinal loyalty within Korea (Han, Kim, & Kim, 2011).…”
Section: Resultantmentioning
confidence: 96%
“…In addition the overall service quality including reliability and responsiveness can be considered as cognitive evaluations of performance over time which can be anticipated to build affective attachment (Thaichon, Quach, & Lobo, 2013). Positive overall service quality impacts on commitment that customers have toward a particular brand and the associated service provider (Jahanzeb, Fatima, & Khan, 2011).…”
Section: Cognitive and Affective Evaluations Of Customersmentioning
confidence: 99%
“…Jahanzeb et al (2011) examined customer loyalty in 146 customers using cell phones in the Pakistani telecommunication industry and found customer loyalty to be shaped predominantly by: service quality, trust, switching cost and staff loyalty. A study of Malaysian telecommunication operators reveals that service quality is most important in the selection of a mobile phone operator followed by network quality and price (Rahman et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%